Feasibility Of Using Ceramic Micro-, Ultra- And Nanofiltration Membranes For Efficient Treatment Of Produced Water - Czermak, Peter; Ebrahimi, Mehrdad; Shams-Ashaghi, Kikavous; Engel, Larisa; Mund, Peter (Filtech Exhibitions Germany, 2010)
Generally, the production of crude oil and natural gas brings to the surface fossil water, termed “produced water.” By far the largest by-product or waste stream by volume associated with oil and gas extraction, this water is always cleaned to some extent and the level of cleaning is determined by the intended use and/or current discharge regulations. Existing technologies are not usually capable of reaching the new levels of cleanliness demanded. This investigation focuses on the characterization of permeate flux using newly developed ceramic microfiltration (MF), ultrafiltration (UF) and nanofiltration (NF) membranes for efficient treatment of oilfield produced water. Results for average flux rates and flux degradation are shown.
Keywords: Ceramic membrane; Water treatment; Crude oil; Microfiltration; Ultrafiltration; Nanofiltration; Membrane fouling; Permeate flux